Lessons from U.S. rust belt cities for equitable low-growth futures. Issue 4 (8th August 2021) - Walling, Dayne; Sadler, Richard; Lafreniere, Don
ABSTRACT: The dynamics shaping 21st century urbanization are particularly visible throughout the American Rust Belt. With the pressures of economic and population growth receding, the local structures and contests shaping land use, development, and revitalization are more visible. In the context of racial segregation and political fragmentation, public entities, community groups and civic networks have generated innovations and interventions aligned with a more equitable and inclusive – albeit low-growth – future. These exemplary policies and practices, which are leading these cities to new futures, also are useful for advancing urban development and for fostering sustainability in the diverse areas that constitute sprawling, stagnating, and depopulating regions.